Antidiabetic drugs and non-alcoholic fatty liver disease: A systematic review, meta-analysis and evidence map. Issue 1 (January 2021) - Kumar, Jai; Memon, Roha Saeed; Shahid, Izza; Rizwan, Tehlil; Zaman, Maryam; Menezes, Ritesh G.; Kumar, Sarwan; Siddiqi, Tariq Jamal; Usman, Muhammad Shariq
Abstract: Background: The efficacy of antidiabetic agents for the treatment of non-alcoholic fatty liver disease (NAFLD) remains unclear. Aim: To conduct a meta-analysis to study the efficacy of pioglitazone and three novel anti-diabetic agents: glucagon-like peptide-1 (GLP-1) agonists, sodium-glucose co-transporter-2 (SGLT2) inhibitors, and dipeptidyl-peptidase-4 (DPP4) inhibitors in treating NAFLD. Methods: Online databases were searched in May 2020 for randomized clinical trials. Results from random-effects meta-analysis are presented as weighted mean differences (WMDs) or standard mean differences (SMDs) and corresponding 95% confidence intervals (CIs). Results: Twenty-six studies (n=946 NAFLD patients) were included. Reductions in ALT were seen with all four drugs: pioglitazone (MD -38.41, p<0.001), SGLT2 inhibitors (MD -16.17, p<0.001), GLP-1 agonists (MD -27.98, p=0.04) and DPP-4 inhibitors (MD -7.41, p<0.001). Pioglitazone (SMD -1.01; p<0.001) and GLP-1 agonists (SMD -2.53, p=0.03) also demonstrated significant improvements in liver steatosis. SGLT2 inhibitors (SMD -4.64, p=0.06) and DPP-4 (SMD -2.49, p=0.06) inhibitors trended towards reduced steatosis; however, these results were non-significant. Conclusion: Pioglitazone demonstrates significant improvements in transaminases and liver histology in both diabetic and non-diabetic NAFLD patients. Early evidence from diabetic NAFLD patients suggests that novel antidiabetics may lead to improvements in liver enzymes and hepatic steatosis, and this should encourage further research into possible utility of these drugs in treating NAFLD.